2017
DOI: 10.1002/2016ja023583
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous space and ground‐based observations of a plasmaspheric virtual resonance

Abstract: We present simultaneous space and ground‐based observations of Pi2 pulsations which occurred during a substorm on 25 September 2014. The timeline for this event starts at ∼06:04 UT when the THEMIS probe D located inside the plasmasphere detected Pi2 pulsations in the electric and magnetic fields. Cross‐spectral analysis shows the azimuthal electric field and compressional magnetic field oscillated nearly in quadrature, highly suggestive of a standing fast‐mode wave. Simultaneous Pi2 observations from dayside a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 66 publications
5
25
0
Order By: Relevance
“…The frequencies and amplitudes of Pi2 waves such as PVR are strongly affected by the plasmapause location. The present study extends previous work relating Pi2 wave activity to plasmapause location (e.g., Ghamry et al, ; Shi et al, ; Takahashi et al, , ) by examining wave activity during an extended interval with stable plasmapause location and variable geomagnetic activity. The following items summarize our key findings: Multiple‐satellite passes and PTP simulations indicate that the plasmapause location is stable for at least 2 h over a wide range of MLT.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The frequencies and amplitudes of Pi2 waves such as PVR are strongly affected by the plasmapause location. The present study extends previous work relating Pi2 wave activity to plasmapause location (e.g., Ghamry et al, ; Shi et al, ; Takahashi et al, , ) by examining wave activity during an extended interval with stable plasmapause location and variable geomagnetic activity. The following items summarize our key findings: Multiple‐satellite passes and PTP simulations indicate that the plasmapause location is stable for at least 2 h over a wide range of MLT.…”
Section: Discussionsupporting
confidence: 79%
“…PVR can also have finite wave amplitudes both inside and outside the plasmasphere (Lee & Kim, 1999). Observational studies have confirmed the existence of PVR, and they have frequencies in the Pi2 range (Ghamry et al, 2015;Luo et al, 2011;Nosé, 2010;Shi et al, 2017;Takahashi et al, 2009;Teramoto et al, 2011); they may also be classified as Pc4 waves (e.g., Takahashi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the observed wave was a cavity mode resonance which had been stimulated by compressional waves which had propagated duskward from the source region in the midnight sector. Shi et al (2017) provided a careful and thorough analysis of multiple data sets from THEMIS, ground magnetometer, and FHE, FHW, and BKS. Shi et al (2017) attempted here to separate a plasmaspheric virtual resonance (PVR) where wave energy is primarily confined to the plasmasphere but a small portion escapes beyond the plasmapause, from a plasmaspheric cavity resonance (PCR) where wave energy should be confined to the plasmasphere.…”
Section: Pi2 and Pi1 Pulsationsmentioning
confidence: 99%
“…Shi et al (2017) provided a careful and thorough analysis of multiple data sets from THEMIS, ground magnetometer, and FHE, FHW, and BKS. Shi et al (2017) attempted here to separate a plasmaspheric virtual resonance (PVR) where wave energy is primarily confined to the plasmasphere but a small portion escapes beyond the plasmapause, from a plasmaspheric cavity resonance (PCR) where wave energy should be confined to the plasmasphere. The radar data are key as they provide high spatial resolution across the plasmapause as shown in Fig.…”
Section: Pi2 and Pi1 Pulsationsmentioning
confidence: 99%
See 1 more Smart Citation